ANALISIS PROGRAM KEGIATAN USAHA KESEHATAN GIGI SEKOLAH (UKGS) DI PUSKESMAS HALMAHERA - Rizka Eman Yulistianti; Prasko Prasko; Iman Supardan; Nani Kristiani (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2015)
TITLEThe effect of concentration differences of betel leaf water stew to inhibit the growth of Streptococcus mutansABSTRACTIn the human mouth, there are various kinds of microorganisms. The bacteria that play an important role in the formation of plaque is bacteria that is capable of forming extracellular polysaccharide, that bacteria of the genus Streptococcus. Streptococcus bacteria are found in large quantities in patients with plaque caries is Streptococcus mutans One effort to prevent the occurrence of dental and oral diseases is to inhibit the growth of bacteria in the mouth. Red betel leaf can be used to inhibit the bacteria Streptococcus mutans. Streptococcus mutans is the bacterial pathogen.The purpose of this study was to determine the effect of different concentrations of red betel leaves boiled water as the inhibition of the growth of Streptococcus mutans bacteria.This type of research is a quasi experimental approach to post-test design. The study was conducted at the Laboratory of Microbiology to sample the bacteria Streptococcus mutans and simple random sampling technique. This study uses pure Streptococcus mutans bacteria grown on an agar medium, and the water red betel leaf decoction is used in different concentrations. To measure the inhibition of growth of a bacterium that is using a ruler (mm) by looking at the bright zone (clear zone) as free areas by bacteria. Data analysis method used is descriptive quantitative.The results showed the water decoction of red betel leaf has a concentration of 5% inhibition of 9.2 mm, red betel leaves boiled water with a concentration of 10% has the inhibition of 7.77mm, red betel leaves boiled water with a concentration of 15% has the power inhibition of 7.073mm, red betel leaves boiled water with a concentration of 20% has the inhibition of 10.105mm. The conclusion from this study is the difference in concentration of the cooking water red betel leaf have the effect of inhibition on the growth of Streptococcus mutans bacteria. In this research needs to be done further research in order to benefit from the water red betel leaf has more influence on oral health. Keywords : Concentration Water Stew Red Betel Leaf, growth of Streptococcus mutans Bacteria.